Rickets in association with skin diseases and conditions: A review with emphasis on screening and prevention. Issue 5 (24th July 2020) - Litaiem, Noureddine; Chabchoub, Ines; Bacha, Takwa; Slouma, Maroua; Zeglaoui, Faten; Khachemoune, Amor
Abstract: Background: Rickets is a common disease worldwide. In the developed world, its prevalence dramatically decreased but still diagnosed in at‐risk populations. The skin plays a critical role in vitamin D synthesis. Therefore, several skin diseases, especially keratinization disorders, could lead to impaired vitamin D metabolism and vitamin D deficient rickets. Objective: The article aimed to summarize the current knowledge of skin diseases and conditions associated with rickets. Methods: To examine the association between rickets and skin diseases, we performed a systematic review of the literature using PubMed database. The search included studies published from the database inception to August 2019. Results: A total number of 75 articles were included. Identified conditions associated with rickets were ichthyosis being a more common skin diseases, alopecia, epidermal and melanocytic nevi, xeroderma pigmentosum, mastocytosis, psoriasis, and atopic dermatitis. Three types of rickets were identified: vitamin D‐dependent rickets, hypocalcemic vitamin D‐dependent rickets type 2, and hypophosphatemic rickets. Cutaneous skeletal hypophosphatemia syndrome is a newly described and under‐recognized condition. It is defined by the association of epidermal or melanocytic nevi, hypophosphatemic rickets, and elevated levels of fibroblast growth factor 23. Rickets in patients with ichthyosis was mainly due to impaired ability of ichthyotic skin to synthesize vitamin D, poor UV penetration of the skin caused by keratinocyte proliferation, and dark phototype. The latter may be considered a risk factor for rickets in patients with ichthyosis. Conclusion: Despite its rarity, these associations should be properly recognized by dermatologists. Early diagnosis of rickets is important to prevent growth retardation and skeletal deformities.